Micropartículas com clorexidina: caracterização, atividade antimicrobiana contra microrganismos da orofaringe em pacientes de UTI e desenvolvimento de pomada Orabase - Brito, Michelline Cavalcanti Toscano de (2019)
Introduction: Patients in Intensive Care Unit (ICUs) have limiting conditions that elevate microbial growth in the oropharynx, and antimicrobials are fundamental in preventing nosocomial pneumonia in these patients. Objective: To characterize chlorhexidine microparticles as an intermediate pharmaceutical and to evaluate in vitro activity on oropharyngeal microorganisms for orabase ointment development. Methods: Microparticles were prepared with chlorhexidine digluconate as active agent and maltodextrin as excipient, then the microparticles were characterized for uniformity, stability, release time of microparticulate chlorhexidine, microscopy analysis, thermal analysis and infrared evaluation. The analysis of type and prevalence of bacterial species was performed in a database of secretion collection or tracheal aspirate from patients admitted to the Lauro Wanderley University Hospital (HULW-UFPB) ICU, and pH analysis of the test solutions and controls. Microbiological tests were performed on planktonic strains and unispecies biofilm for the efficacy of chlorhexidine microparticles against oropharyngeal microorganisms Staphylococcus aureus, Pseudomonas aeruginosa, Klebsiella pneumoniae, Streptococcus pneumoniae and Candida albicans. In sequence, orabase ointment pharmaceutical form was prepared with 0,12% chlorhexidine microparticles for microbiological and stability testing. Results: The microparticles showed favorable characteristics as intermediate product. In the microscopy analisis, morphology was compatible with preparation process and the incorporation of chlorhexidine in the microparticles was confirmed. Mass uniformity, chemical stability at 24 months, water absorption stability at 12 months were observed, and slow release profile for approximately 2 hours. The Pseudomonas aeruginosa was the most prevalent bacterium in HULW-UFPB patients, and the pH of the solutions was appropriate for microbiological studies. In microbiological tests the chlorhexidine microparticles showed results similar to those observed with free chlorhexidine against all strains studied, and the microparticles ointment had antimicrobial effects compatible with slow release for the same strains. Loss of physical stability with oxidation of the ointment prepared with the microparticles was found, which was attributed to the incompatibility between maltodextrin and the pH neutralizing agent, its replacement and pH adjustments for future non-clinical and clinical tests are suggested. Conclusion: Chlorhexidine microparticles and incorporated into pharmaceutical form of orabase ointment may have clinical intraoral application advantages as a controlled release system.